Mass spectrometry for the characterization of unsulfated chondroitin oligosaccharides from 2-mers to 16-mers. Comparison with hyaluronic acid oligomers - Volpi, Nicola (2008)
This study reports for the first time the complete liquid chromatography/electrospray ionization mass spectrometry (LC/ESI-MS) and tandem mass spectrometry (MS/MS) analyses performed in negative ion mode of saturated unsulfated chondroitin oligosaccharides up to 16-mers and comparison with hyaluronic acid (HA) oligomers differing only in the nature of the hexosamine residue. MS/MS of the chondroitin disaccharide on the singly charged precursor at m/z 396.1 afforded a glycosidic cleavage C(1) product ion at m/z 192.9. In the tetrasaccharide, C(2) (m/z 396.0) and C(3) (m/z 572.0) product anions were generated by glycosidic cleavage. A C(5) [M–2H](2−) production at m/z 475.1 was generated by the glycosidic cleavage of the hexasaccharide, and a C(7) ion (m/z 664.6, charge state of −2) was produced from the octasaccharide. The same fragmentation pattern of deprotonated oligomers was observed for the largest oligosaccharides, from 10- to 16-mers. There has been no previous report of MS/MS spectra for unsulfated chondroitin oligomers of these sizes. Unsulfated saturated chondroitin oligosaccharides with x-mer units and larger than a tetrasaccharide dissociate to almost exclusively form C(X–1)-type ions. Saturated HA oligomers also afforded the same fragmentation pattern as deprotonated oligomers by ESI-MS and MS/MS analyses. Thus, under the experimental conditions used in the current study, we were unable to distinguish between unsulfated chondroitin and HA.